2002
DOI: 10.1095/biolreprod67.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cloned Pigs from Adult Somatic Cells by Chemically Assisted Removal of Maternal Chromosomes1

Abstract: The present study demonstrated that brief treatment of in vitro-matured porcine oocytes with demecolcine results in a membrane protrusion that contains a condensed chromosome mass, which can be easily removed by aspiration. This simple, chemically assisted method for removing maternal chromosomes enabled the production of a large number of nuclear-transferred porcine eggs. The development of eggs whose chromosomes were removed by this procedure following transfer of somatic cell nuclei to the blastocyst stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
176
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(188 citation statements)
references
References 23 publications
9
176
2
1
Order By: Relevance
“…Most previous publications failed to investigate the in vivo development or data collected were insufficient for statistical calculations (Faast et al, 2006;Tomii et al, 2005;Uhm et al, 2000;Yin et al, 2002). Our results confirmed that the capacity of nucleus to be reprogrammed cannot be evaluated exclusively by in vitro development; in contrast, in vivo development may be a more important characteristic.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Most previous publications failed to investigate the in vivo development or data collected were insufficient for statistical calculations (Faast et al, 2006;Tomii et al, 2005;Uhm et al, 2000;Yin et al, 2002). Our results confirmed that the capacity of nucleus to be reprogrammed cannot be evaluated exclusively by in vitro development; in contrast, in vivo development may be a more important characteristic.…”
Section: Discussionsupporting
confidence: 79%
“…Lee et al (2003) reported that more blastocysts were derived from SCNT of FFs than from that of other cells (AFs, cumulus cells, and oviduct cells). Yin et al (2002) reported that, by using FFs, the blastocyst rate was higher than those obtained with adult cells of various origin (cumulus, liver, heart, kidney, muscle, oviduct). The difference may be due mainly to different types of adult-derived donor cells used in our study and those papers.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pig kidney fibroblasts as donor cells for SCNT experiment has been reported by several investigators [8,10,37]. However, to our knowledge, we produced the first cloned miniature piglet derived from kidney cells of an aged adult.…”
Section: Discussionmentioning
confidence: 99%
“…To date, pigs have been produced by SCNT techniques using donor cells derived from fetuses and young pigs [4][5][6][7][8][9][10][11][12][13]. The use of pig kidney fibroblasts as donor cells for SCNT experiment has been reported by several investigators [8,10,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation